Radiological Examinations in Pediatric Age - Siciliano, R (Annali di igiene, 2017)
Diagnostic radiology imaging is an essential tool for adequate clinical investigation of pathological processes and the drafting of a personalized therapy plan. However, in recent years, there has been a substantial increase of requests, mainly due to technological advances but also to social and cultural reasons, not always based on the principle of the diagnostic justification. The progress of recent years in the field of diagnostic radiology has made available to the physician a variety of sophisticated radiological examinations, which are not always used rationally and appropriately. The theme is of paramount importance, particularly in childhood or adolescence, characterized by elevated radiosensitivity (high cell turnover) and longer life expectancy; therefore, children exposed to ionizing radiation are theoretically subject to a higher risk of carcinogenesis compared to the general population. For these reasons the young patients should have greater protection and examinations must respect stringent appropriateness criteria. Far from underestimating the important diagnostic and therapeutic benefits that these procedures provide, the use of ionizing radiations must minimize the radiation-related risk in accordance with the ALARA principle (As Low As Reasonably Achievable), key principle of modern radiation protection.